Badenhausen, George (audio interview #1 of 1) - Badenhausen, George (1904 - 6/16/1905); Andriesse, Ann, interviewer
INTERVIEW DESCRIPTION - This interview was conducted at Badenhausen's home. Another former employee of the Harriman Jones Clinic, Virginia Davis, was also present. 6/11/1984